Мережа аптечних закладів Київської губернії як вид медичної допомоги населенню краю (кінець ХVIII - початок 60-х рр. XIX ст.) - Морей, Т. (Краєзнавство, 2019)
У статті на основі архівних матеріалів та нормативно-правових актів проведено аналіз та визначено фактори, які впливали на отримання дозволу на відкриття аптек, їх місцезнаходження, матеріальне становище та забезпечення медикаментами. Проаналізовано чинники, які впливали на встановлення та обрахунок цін на медичні препарати відповідно до законодавства, а також повноваження органів, які здійснювали контроль за аптечною справою у Київській губернії. Problem statement. The process of reorganization has become an integral part of social-political and economic transformations in Ukraine. Its put on the agenda not only the issue of the need for an effective regional policy, but also the problem of scientific understanding of the preconditions and forming of individual regions of the country in historical and socio-cultural dimensions, the origins of regional self-consciousness. It is particularly important to apply to our own traditions, in this context. For this reason, the state of medicine study in general, and the network of pharmacy establishments functioningin particular, is very important. Particularly, in one of the largest Ukrainian provinces – Kyiv. It is essential to the understanding of the patterns and peculiarities of the health care system formation in certain regions. Research methods. During the study of the problem, multiple research methods were used including the following: general scientific, special, source-study, general-historical, interdisciplinary. Description of the results. The article describes the foundation and functioning of the pharmacy institutions network in Kiev province at the end of the 18th and early 1860s. It is based on the analysis of archive materials and legal acts and shows the main factors that allowed obtaining permissions to open pharmacies, their locations, financial situation, and medicines provision. Using the Kyiv province as an example, the article researches the changing dynamics of the pharmacies number depending on the year and identified that most of them were private property. The number of pharmacies in each region was dependent on the population and permitted recipes. The article analyses the factors that were used to calculate and set the prices for medicals according to the legislation, and also the authorities who controlled the pharmacy industry within the province. In particular, official duties of Kyiv medical administration in supervision and inspection of pharmacies, and decisions that were made by the Medical Department of MVS regarding the pharmacies owners after filling inspection protocols. Conclusions. The worked out archival documents, materials and published sources, testify that the end of the 18th and 60th years of the XIX century were the period of development of the pharmacy establishments network in the Kiev province.